The brown rot fungi of fruit crops (Monilinia spp.): I. Important features of their biology (Review paper) - Holb, I. J. (International Journal of Horticultural Science, 2003)
The brown rot fungi of fruit crops (Monilinia spp.): Important features of their biology (Review paper)